Imaging of the region of the osteochondral junction (OCJ) using a 3D adiabatic inversion recovery prepared ultrashort echo time cones (3D IR‐UTE‐cones) sequence at 3 T. (22nd February 2019) - Ma, Ya‐Jun; Jerban, Saeed; Carl, Michael; Wan, Lidi; Guo, Tan; Jang, Hyungseok; Bydder, Graeme M.; Chang, Eric Y.; Du, Jiang
Abstract : The purpose of this study is to develop a 3D adiabatic inversion recovery prepared ultrashort echo time Cones (3D IR‐UTE‐Cones) sequence for high resolution and contrast imaging of the region of osteochondral junction (OCJ) of human knee joint using a clinical 3 T scanner. A feasibility study on direct imaging of the OCJ region was performed on a human patellar cartilage sample and on eight cadaveric knee joints using T 1 ‐weighted, proton density (PD)‐weighted and short‐ T 2 ‐weighted 3D IR‐UTE‐Cones sequences. Contrast to noise ratio was measured to evaluate the effectiveness of the 3D IR‐UTE‐Cones sequences for selective imaging of the OCJ region. Computed tomography imaging was performed in parallel for the cadaveric knee joints. The optimized T 1 ‐weighted 3D IR‐UTE‐Cones sequence was used to image the knee joints of eight healthy volunteers and six patients with osteoarthritis (OA) to evaluate morphological changes in the OCJ region. Clinical PD‐ and T 2 ‐weighted FSE sequences were also performed for comparison. The T 1 ‐weighted 3D IR‐UTE‐Cones sequence showed high resolution and contrast bright band of the normal OCJ region in the cadaveric joints. Normal OCJ appearances were also seen in healthy volunteers. Abnormal OCJ regions, manifested as ill‐defined, focal loss or non‐visualization of the high intensity band adjacent to the subchondral bone plate, were observed in the knee joints of both ex vivo and in vivo OA patients. The 3D IR‐UTE‐Cones sequence can image OCJ regions ex vivo and in vivo, with abnormalities depicted with high resolution and contrast. The technique may be useful for demonstrating involvement of OCJ regions in early OA. Abstract : Osteochondral junction region imaging of a normal knee joint specimen from a 31‐year‐old male donor. The clinical images (PD‐FSE in first column and T2 ‐FSE in second column) are used for comparison with the T1 ‐weighted IR‐UTE‐Cones images (third column). The IR‐UTE‐Cones images show high OCJ contrasts (i.e. bright band), which can be seen more clearly in the zoomed images. The last column is the fat‐saturated UTE‐Cones images for comparison. These show signal from both uncalcified and calcified cartilage.